Work load analysis for determining the optimal employee number – a case of Faculty of Economics Pakuan University Bogor, Indonesia / Herman and Geetha Subramaniam - Herman, Herman; Subramaniam, Geetha (UiTM Press, 2018)
Generally, the number of employees in an organisation needs to be based on the workload of the administrative staff and this is practised at the Economic Faculty Pakuan University, Indonesia too. To calculate the activity time of employees who work or not, researchers use the work sampling table. The method of calculating labour requirements is based on the calculation of the workload with the task per duty of the office according to Government guidelines. In Indonesia, the guidelines are spelt out in detail in the government document MenPAN No. KEP/75/M.PAN/7/2004 namely the “Guidelines for Employee Needs Calculation”. Samples on employee status were extracted from the Economics Faculty of the Pakuan University from the principal administrative officer. Data was processed using Microsoft Excel. The study concluded that there is a significant result in the use of working time and found that the University had the required number of employees it needed whereby 3 functions of services were done by 9 persons. Based on the calculation of the workload analysis, one more employee is needed for the financial services. It was also noted that efficiency level for effective working hours for administrative staff is 28 hours per week or 1680 minutes and there is a smooth workload administration at the Faculty of Economics. However, an additional employee in the Administration Department and an additional academic staff will increase the efficiency of employees in the Faculty.